Antimicrobial Resistance Patterns of Escherichia coli Among Visitors of Pathology Centers in Gharyan - Almshawit, Hala; Shagshog, Retaj; Aldib, Hana; Areebi, Sarah; Tahar, Weam (AlQalam Journal of Medical and Applied Sciences, 2025)
The collection of comprehensive data is crucial for monitoring antimicrobial resistance (AMR) patterns and implementing targeted interventions. However, there is a lack of data regarding the AMR status of pathogens in Libya, hinders the efforts to address the problem effectively. This retrospective study evaluates the prevalence of Escherichia coli AMR isolates to gentamycin, chloramphenicol, cefoxitin (or) ceftriaxone, meropenem, moxifloxacin (Mox), amoxicillin/clavulanate (AUG) or ampicillin-sulbactam (UNZ) among the visitors to the main pathology laboratories in Gharyan city. Reports from 107 AMR tests demonstrate that E. coli was mostly isolated from Urinary Tract Infections (UTIs, 85%) followed by vaginal infections (8.4%) and wound infections (6.5%). More than half of the isolates were multi-drug resistant which is a clear indicator of the need for continuous monitoring. The overall pattern demonstrates a high resistance rate to cephalosporins, and combinations of penicillins with beta-lactamase inhibitors (UNZ or AUG), followed by high resistance rates to Mox. In contrast, E. coli isolates showed high sensitivity to meropenem followed by gentamicin and chloramphenicol. However, the isolation site seems to affect the resistance patterns, most of the wound isolates were resistant to gentamycin. In contrast, all vaginal isolates were resistant to UNZ or AUG, yet both types showed high susceptibility to meropenem. تجميع بيانات عن معدلات انتشار مقاومة المضادات الميكروبية في المجتمع يُعتبر أمرًا بالغ الأهمية في مواجهة التحديات الصحية، وذلك عن طريق المراقبة وتنفيذ التدخلات المطلوبة. هناك نقص في البيانات المتعلقة بمعدلات مقاومة مضادات الميكروبات لمسببات الأمراض في ليبيا، مما يعيق الجهود الرامية إلى معالجة المشكلة بشكل فعال. تُقيّم هذه الدراسة معدل انتشار مقاومة عزلات من الإشريشية القولونية لمجموعة من المضادات الحيوية بين زوار أهم مختبرات التحاليل الطبية في منطقة غريان. المضادات الحيوية التي تضمنتها الدراسة هي الجنتاميسين، والكلورامفينيكول، والسيفوكسيتين (أو) السيفترياكسون، والميروبينيم، والأمبيسيلين-سولباكتام (أو) الأموكسيسيلين- كلافولانات، والموكسيفلوكساسين. أظهرت نتائج 107 اختبار حساسية للمضادات الحيوية أن الإشريشية القولونية كانت معزولة في الغالب من عينات البول (85%)، تليها العينات المهبلية (8.4%) ومسحات الجروح (6.5%). كما أنه أكثر من نصف العزلات أظهرت مقاومة متعددة للأدوية، وهذا مؤشر مهم عن الحاجة إلى المراقبة المستمرة. يوضح النمط العام للنتائج معدلات مقاومة عالية للسيفالوسبورينات ومجموعة البنسلينات المدعمة بمثبطات البيتا لاكتاميز، تليها معدلات مقاومة مرتفعة للموكسيفلوكساسين. بالمقابل أظهرت نتائج الاختبارات حساسية العزلات للميروبينيم تليها الجنتاميسين والكلورامفينيكول. كما أن موقع العزل يبدو أنه عامل مُؤثر على أنماط المقاومة، فمعظم عزلات الجروح مقاومة للجنتاميسين بينما العزلات المهبلية كانت مقاومة للبنسيلينات المدعومة بمثبطات البيتالاكتاميز. في حين كلاهما أظهر حساسية عالية للميروبينم